Customary Law as a Legal Basis in Disputes over Customary Land Rights - Hendrina Clotilda Difa Fernandez; Darius Mauritsius; Petornius Damat (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
This study aims to analyze the customary legal basis for the acquisition of ulayat land rights and the legal consequences of Decision Number 20/Pdt.G/2024/PN Lrt on the de facto and de jure status of disputed ulayat land in East Flores Regency. This research employs a normative legal method with statutory, case, historical, comparative, and conceptual approaches. The results show that the customary legal basis for acquiring ulayat land rights originates from Lamaholot customary law as a living law that is recognized and practiced across generations through mechanisms such as ancestral inheritance, customary land transfer, customary oaths, territorial division, and marriage practices as a substitute for bridewealth (belis). The existence of ulayat rights in this case fulfills the elements of a customary law community, the existence of ulayat land, and a functioning customary legal system as stipulated in Article 2 paragraph (2) of the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 5 of 1999. The court decision declaring the claim inadmissible (niet ontvankelijke verklaard) is limitedly declarative and does not address the merits of the case. De facto, the land remains controlled and utilized by the customary community, while de jure, its legal status remains uncertain. Thus, this decision reflects a separation between social reality and legal certainty and highlights the importance of clearly defining legal subjects and objects in ulayat land dispute claims.